Evaluation of Molecular Point-of-Care Testing for Respiratory Pathogens in Children With Respiratory Infections: A Retrospective Case-Control Study - Shen, Nan; Zhou, Yuanjie; Zhou, Yajuan; Luo, Lijuan; Chen, Wenjuan; Wang, Jing; Zhao, Ruike; Xie, Li; Cao, Qing; Tao, Yue; Mo, Xi (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives: Overuse of antibiotics and antibiotic resistance are global healthcare problems. In pediatric patients with respiratory infections, viral and bacterial etiologies are challenging to distinguish, leading to irrational antibiotic use. Rapid and accurate molecular diagnostic testing methods for respiratory pathogens has been shown to facilitate effective clinical decision-making and guide antibiotic stewardship interventions in the developed regions, but its impacts on pediatric patient care in the developing countries remain unclear. Methods: In this single-center, retrospective case-control study, we compared demographics, clinical characteristics, especially microbiological findings, and antibiotic usage between pediatric patients with respiratory infection receiving FilmArray Respiratory Panel (FilmArray RP) testing and a matched routine testing control group. Our primary outcome was the duration of intravenous antibiotics treatment (DOT) during hospitalization. Results: Each group consisted of 346 children with a respiratory infection. In the FilmArray RP testing group, the DOT was shorter than that in the routine testing group (6.41 ± 3.67 days versus 7.23 ± 4.27 days; p = 0.006). More patients in the FilmArray RP testing group de-escalated antibiotic treatments within 72 hours of hospitalization (7.80%, 27/346 versus 2.60%, 9/346; p = 0.002). By contrast, fewer patients in the FilmArray RP testing group had escalated antibiotic treatments between 72 hours and seven days (7.80% versus 14.16%; p = 0.007). The cost of hospitalization was significantly lower in the FilmArray RP testing group ( 1413.51 ± 1438.01 versus 1759.37 ± 1929.22; p = 0.008). Notably, the subgroup analyses revealed that the FilmArray RP test could shorten the DOT, improve early de-escalation of intravenous antibiotics within 72 hours of hospitalization, decline the escalation of intravenous antibiotics between 72 hours and seven days, and reduce the cost of hospitalization for both patient populations with or without underlying diseases. Conclusions: Molecular point-of-care testing for respiratory pathogens could help to reduce intravenous antibiotic use and health care costs of pediatric patients with respiratory infections in developing countries.